SPATIAL AND TEMPORAL VARIABILITY OF RAIN EROSIVITY (EI30) IN THE STATE OF SÃO PAULO, BRAZIL - Ricardi, Amanda De Moraes [UNESP]; Lima, César Gustavo Da Rocha [UNESP] (UNESP - Universidade Estadual Paulista, 2021)
Rain erosivity is an important variable in the diagnosis of soil loss in predictive models. From the database of pluviometric posts of the Department of Water and Electricity (DAEE), the objective was to study the monthly and annual rainfall erosivity rates (EI30), and to evaluate the space-time variability in the state of São Paulo, in the periods 1987-2007 and 1997-2017. Descriptive and geostatistical statistical analysis of the data was performed. Data analysis indicated greater variability in seasonal transitional periods. Spatially, the spatial determination coefficient (R²) ranged between 0.800-0.992. The range (A) also indicated seasonal influence, varying between 126,000-608,000m (monthly) and 423,832-682,000m (annual). The cross-validation showed correlation coefficients (r) varying between 0.658-0.974 (monthly) and 0.799-0.835 (annual) indicating appreciable maps generated by ordinary kriging. The spatial analysis allowed to infer that in the dry period there was an increase in monthly erosivity in the southern direction of the state; while in the rainy season the opposite occurred. In the most recent period (1997-2017), annual erosivity was between 6,019-8,699 MJ mm ha-1 h-1 ano-1. Such results indicated a spatio-temporal evolution over the studied periods and represent recent estimates that can be widely used in predictive models of soil loss in the state.
VARIABILIDADE CHUVAS (EI30) NO ESTADO DE SÃO PAULO, BRASIL
Keywords: Geoestatistic; Soil management and conservation; Universal Soil Loss Equation; Water erosion